1998
DOI: 10.1136/hrt.80.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic dilated cardiomyopathy: lack of association with hepatitis C virus infection

Abstract: Objective-To determine whether there is an association between hepatitis C virus (HCV) infection and dilated cardiomyopathy in a well defined area of north western Greece; such an association has been reported elsewhere. Design-Evaluation of consecutive patients with chronic HCV infection for the presence of clinical or subclinical manifestations of dilated cardiomyopathy by history, physical examination, and noninvasive laboratory procedures (ECG, chest x ray, and echocardiography) before the initiation of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Other reports of HCV prevalence in patients with IDC reported from 0% [23,25] to 16.6% [12]. However, in this latter paper, Matsumori does not exclude all possible etiologies of dilated cardiomyopathy, so they cannot be considered as idiopathic.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Other reports of HCV prevalence in patients with IDC reported from 0% [23,25] to 16.6% [12]. However, in this latter paper, Matsumori does not exclude all possible etiologies of dilated cardiomyopathy, so they cannot be considered as idiopathic.…”
Section: Discussionmentioning
confidence: 71%
“…Only one paper looked for IDC in a cohort study involving patients with confirmed HCV infection [23]; in all other studies the investigation process occurred inversely. Most were defined as transversal studies; though there were also prospective followup studies of HCV-infected patients ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations